Fibrinogen Concentrates for Acquired Fibrinogen Deficiencies? - Samama, Charles Marc (Seminars in Thrombosis and Hemostasis, 2016)
Surgical bleeding has been decreasing steadily for the last 20 years, but there are still some hemorrhagic procedures occurring in scheduled surgical settings and emergency procedures. The interest in potent hemostatic agents has recently focused on fibrinogen concentrates. A weak historical rationale based on the rapid decrease in fibrinogen concentration in the bleeding patient and several uncontrolled studies have prompted the use of fibrinogen concentrates in emergency units and in operating theaters. Very few positive randomized studies are available to confirm the usefulness of fibrinogen concentrates. The largest most recent double-blind studies are even negative. As recent guidelines recommend early and liberal use of fibrinogen concentrates in massive bleeding patients, this review reports the most important facts and studies on efficacy and raises some questions about safety.
Keywords: fibrinogen concentrates; bleeding; transfusion; thrombosis